PEDAGOGICAL SIGNIFICANCE OF THE SPORTS MEDICINE APPROACH TO THE EDUCATIONAL PROCESS - Akbarova D. R. (Bright Mind Publishing, 2025)
The article details the pedagogical significance of the approach to sports medicine in the field of physical education in terms of improving the professional training of the teacher and the main concepts and foundations of sports medicine.
Keywords: Physical education teacher, sports medicine, concept, diagnosis, rehabilitation, criterion, athlete, pedagogical yondshuv, social, psychological, health.